Differential effects of exposure to cooperative versus competitive games on sharing behavior in young children - Zhang, Qian; Ruan, JiaLe; Xiong, DingYong (Frontiers in Psychiatry, 2025)
BackgroundPrevious research has documented a relationship between prosocial video games and prosocial behaviors. However, there has been much less evidence on the potential effects of real-life prosocial games. Theoretically, games in which characters cooperate and help each other in nonviolent ways should increase prosocial behavior.ObjectiveIn this study, we experimentally evaluated the effects of competitive and cooperative games on sharing behavior.MethodsThe study sample were 120 children (Mage = 4.73 years, SD = 0.49) from two kindergartens in China. Participants were randomly assigned to play the same game for 15 minutes in either a cooperative or competitive setting. Then their sharing behaviors were measured. A 2(Setting) × 2 (Gender) Analysis of Covariance (ANCOVA) was performed, controlling for age.ResultsResults indicated that playing a cooperative game (versus competitive game) increased sharing behavior. In addition, we observed a Setting × Gender interaction. Basically, boys’ sharing attitudes and behaviors were unaffected by the Setting manipulation, whereas girls’ were affected. Similarly, the competitive setting increased girls’ sharing attitudes and behaviors, whereas the boys’ was relatively unaffected. Precisely, girls reported more sharing behavior than boys in competitive gaming condition.ConclusionFindings of this study suggest that educational practitioners can utilize a cooperative game (versus competitive game) as an effective way to develop sharing behavior among kindergarten children. Boys should be a target group for sharing behavior development, especially in a competitive game setting.